Bioetanol dari Limbah Kulit Singkong (Manihot Esculenta Crantz) Melalui Proses Fermentasi - Erna, Erna; Said, Irwan; Abram, Paulus Hengky (Jurnal Akademika Kimia, 2016)
Carbohydrates can be obtained from tubers such as cassava. Cassava is a plant from family euphorbiaceae and typical tropical plants. Cassava peel is a major waste that contains carbohydrates. The peel of cassava can be used as an energy source, namely ethanol.The purpose of this study is to determine the contents of ethanol through the fermentation process of cassava peel where obtainable from Malino village, Batu Daka West, Tojo Una-Una. The parameters in this study was content of ethanol that was obtained by fermentation using saccaromyces cerevisiae yeast. The fermentation process was conducted by varying day of fermentation, 4, 6, 8, and 10 days. The results showed the fermentation of ethanol with time variation respectively is 4.50, 5.20, 6.00 and 4.00%. In conclusion, it can be said that the highest ethanol content is 6.00% with the fermentation time of 8 days.